Exploring the Correlation Between Nursing Management Functions and Nurse Mentorship Implementation in Clinical Practice - Sitorus, Evalina; Winarsih, Winarsih; Sihombing, Riama Marlyn; Theresia (Yayasan Rumah Ilmu Professor, 2025)
Mentoring has been recognized as a valuable approach to decreasing turnover and enhancing nursing quality management indicators. The mentor must possess managerial functions to accomplish the objectives of mentorship. The mentors must perform management functions for mentees during the mentoring process, such as creating a comfortable and safe learning environment, assisting mentees in problem solving, jointly finding solutions, providing reinforcement, and empowering mentees by honing mentees' abilities to improve their competence. This study sought to determine the correlation between nursing management duties and the execution of nurse mentorship at a private hospital located in West Indonesia. The research design employed a quantitative correlational methodology utilizing a cross-sectional approach. The research participants consisted of 43 mentees recruited by a complete sample technique. The research employed a Likert scale questionnaire and analyzed data using chi-square methods. There is a significant statistical relationship between nursing management functions and implementation of mentorship (p<0.001). The study concluded that nursing management functions correlated significantly with the implementation of nurse mentorship in the hospital.